Temporal Dynamics of Endogenous Bacterial Composition in Rice Seeds During Maturation and Storage, and Spatial Dynamics of the Bacteria During Seedling Growth - Dutta, Swarnalee; Choi, Soo Yeon; Lee, Yong Hoon (Frontiers in Microbiology, 2022)
Seed endophytes are of particular interest because they affect seed quality and, ultimately, plant growth and fitness. However, a comprehensive understanding of the assembly of the seed microbiome during seed development and maturation, fate of the microbes during storage, and migration of the microbes during seedling growth is still lacking. In this study, to understand the assembly and fate of endogenous bacteria in rice seeds from the ripening stage to the storage and seedling stages, we employed culture-dependent and metagenomic analyses. Bacterial communities in rice seeds were composed of a few dominant taxa that were introduced at the milky and dough stages, and they persisted during seed maturation. The culturable bacterial population gradually increased during the ripening stage, whereas there was a gradual decrease during storage. Bacteria that persisted during storage proliferated after imbibition and were distributed and clearly established in the shoots and roots of rice seedlings. The storage temperature influenced the abundance of the bacteria, which consequently changed the bacterial composition in the shoots and roots of seedlings. Pantoea, Pseudomonas, and Allorhizobium were constantly abundant from seed development to the germination stage. Some endogenous bacterial strains significantly promoted the growth of Arabidopsis and rice plants. Overall, our results indicate that rice seeds are colonized by a few bacterial taxa during seed development, and their relative abundance fluctuates during storage and contributes significantly to the establishment of endophytes in the stems and roots of rice plants. The selected bacterial isolates could be used to improve the growth and health of rice plants. To the best of our knowledge, this is the first study to reveal the dynamics of bacterial populations during the storage of rice seeds at different temperatures. The temporal dynamics of the bacterial community during seed storage provides clues for the manipulation of endogenous bacteria in rice plants.